2015
DOI: 10.5014/ajot.2015.016287
|View full text |Cite
|
Sign up to set email alerts
|

Activity Pacing Self-Management in Chronic Fatigue Syndrome: A Randomized Controlled Trial

Abstract: OBJECTIVE. The objective of this study was to evaluate the effectiveness of an activity pacing self-management (APSM) intervention in improving performance of daily life activities in women with chronic fatigue syndrome (CFS). METHOD. A total of 33 women with CFS (age 41.1 ± 11.2 yr) were randomly allocated to APSM (experimental group; n = 16) or relaxation (control group; n = 17). Main outcome measures included the Canadian Occupational Performance Measure (COPM; primary) and Checklist Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 54 publications
1
81
0
Order By: Relevance
“…In MS, an individualized outpatient rehabilitation program including occupational therapy focusing on energy conservation did not show any changes in fatigue (impact) scores, which is in line with our findings (Rietberg et al, 2014). However, a similar individual program did show improvements both in COPM and in fatigue scores in patients with chronic fatigue syndrome (Kos et al, 2015). These results may suggest that group dynamics are highly important in reducing fatigue (impact) scores in patients with MS, but no studies have as yet compared individual and group approaches.…”
Section: Discussionsupporting
confidence: 93%
“…In MS, an individualized outpatient rehabilitation program including occupational therapy focusing on energy conservation did not show any changes in fatigue (impact) scores, which is in line with our findings (Rietberg et al, 2014). However, a similar individual program did show improvements both in COPM and in fatigue scores in patients with chronic fatigue syndrome (Kos et al, 2015). These results may suggest that group dynamics are highly important in reducing fatigue (impact) scores in patients with MS, but no studies have as yet compared individual and group approaches.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a group-based self-management program for chronic fatigue syndrome patients seems to be useful in relief of fatigue severity, despite unsustained at the one-year follow-up, [67] therefore, it is needed to support CFS/ME patients to access reliable, evidence-based information outside primary care, and an online resource for patients to support self-management may be a good choice [68]. In addition, activity pacing self-management was also found to be feasible and effective in desired daily life activities and reducing fatigue in women with CFS [69]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, participating in these courses can be very difficult because they require attendance at in-person treatment sessions. This is problematic because instances of PEM are associated with changes in routine, prolonged cognitive effort, and travelling [40]. Individuals with ME/CFS have reported that their symptoms worsen as a result of participating in such programs [29] and thus many receive no formal treatment for their condition [32].…”
Section: Self-management For Me/cfsmentioning
confidence: 99%
“…One of the immediate challenges of conducting research with ME/CFS patients is that it is unclear how their involvement might exacerbate the symptoms of their condition. As noted above, some patients can suffer serious consequences when deviating from set routines [40] and thus participation in a research study could cause undue harm by inducing PEM, for example. This presents major challenges in terms of configuring their involvement, not just from a practical perspective (what techniques should be employed to involve patients?)…”
Section: Recruitment and Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation